PENYUSUNAN JALUR EVAKUASI BANJIR SUNGAI GAJAH WONG WARUNGBOTO DALAM MENDUKUNG DESA TANGGUH BENCANA KOTA YOGYAKARTA - M.A, Budiyanto; Nurokhman, Nurokhman; M., Arifin (Universitas Cokroaminoto Yogyakarta, 2025)
The Gajahwong Warungboto River Bank Area Yogyakarta has been arranged into an environmentally and residential area with the concept of a Backward house, MUpload Madep Kali (M3K). In 2021 due to heavy rain, there was a flood in Warungboto Village which caused talut to collapse and affected residents' homes around the riverbanks. The problem at the location, especially RW 09 and RW 08, is the lack of disaster mitigation facilities, the lack of smooth drainage channels in areas blocked by river embankments because the position of the flood water level is higher than the drainage outlet channels, so that water collects at a certain point. The results of surveys and interviews are taken into consideration in carrying out activities. Preparation of evacuation routes to provide solutions during flood events by mapping flood inundation areas from the overflow of the Gajahwong River and establishing evacuation routes / access for affected people to a safe location from flood overflow / inundation. After community dedication, community readiness in evacuation activities during flood disasters is better and directed based on evacuation routes that have been prepared. As a recommendation for an approach to increase understanding of disaster mitigation in potential impacts and increase partnerships for the sustainability of synergy in handling flood disaster problems in the riverbank area.